Binding mechanism and SERS spectra of 5-fluorouracil on gold clusters - Si, Nguyen Thanh; Nhat, Pham Vu; Nguyen, Minh Tho (Frontiers in Chemistry, 2022)
The adsorption behaviour of the 5-fluorouracil (5FU) on small gold clusters AuN with N = 6, 8, 20 was evaluated by means of density functional theory using the PBE-D3 functional in combination with a mixed basis set, i.e. cc-pVDZ-PP for gold atoms and cc-pVTZ for non-metal elements. The binding energies between 5FU and gold clusters were determined in the range of 1624 and 1119 kcal/mol in gas-phase and aqueous media, respectively. The corresponding Gibbs energies were found to be around -7 to -10 kcal/mol in vacum and sigificantly reduced to -1 to -6 kcal/mol in water solution, indicating that both the association and dissociation processes are likely spontaneous. An analysis on the charge density difference tends to confirm the existence of a charge transfer from 5FU molecule to Au atoms. Analysis of the surface-enhanced Raman scattering (SERS) spectra of 5FU adsorbed on the Au surfaces shows that the stretching vibrations of NH and C=O bonds play a major role in the SERS phenomenon. A mechanism for the drug releasing from the gold surfaces is also proposed. The process is triggered by either the low pH in cancerous tumors or the presence of cysteine residues in protein matrices.